(untitled) (Conferencea, 2021)
In the development of poultry, taking into account the breed, age, weight, productivity of birds, it is important to keep them in zoohygienic conditions and to establish a nutritious diet. The development of the global livestock industry shows that the production of poultry meat is growing faster than any other animal species in terms of meat production. The reason for the spread of poultry is that it lays a lot of eggs throughout the year and quickly reaches the meat. There is a growing interest in poultry farming due to the rapid growth of broiler chickens and the production of high-quality cheap meat relative to consumed feed, short-term cost recovery and the growing demand of the population for dietary poultry meat.